A comparative study of modified Bassini’s repair and Lichtenstein’s repair for indirect inguinal hernia in young age population - Zahoor, Adnan; Charokar, Kailash; Singh, Piyush (International Surgery Journal, 2024)
Background: Inguinal hernia surgery has significant world-wide diversity in management. European Hernia Society guidelines 2020, for management of groin hernias recommends the use of open non-mesh repair in specific patients or types (e.g. young males with lateral hernia)as an acceptable alternative to a Lichtenstein technique. The present study deals with the comparison of intra operative, postoperative course and clinical outcome of modified bassinis repair (non mesh) and Lichtenstein repair [mesh repair] for indirect inguinal hernia in young age population. Methods: Observational analytical prospective cohort study, conducted in General Surgery, Peoples hospital, Bhopal from November 2022 to February 2024. Patient of indirect inguinal hernia in the age (16-35 years) group and operated by either Modified Bassinis (Group A, n=34) or lichtenstein hernia repair (Group B, n=48). The above study arms group were studied and compared. Results: Mean duration of surgery among Group A patients was 62.65 minutes and 57.19 minutes in Group B. Seropurulent discharge among 2.9% patients in Group A and 4.2% in Group B and superficial SSI among 2.9% patients in Group A and 4.2% in Group B was reported. Chronic post-operative pain VAS score was assessed at end of 2nd week, end of 1 month and end of 3 months with statistically no significant among two groups. Conclusions: Our study did not demonstrate any significant difference of one repair method over the other. However, an Individualized approach for cases with a customized strategy is recommended for surgical management of hernia.